Pengaruh nilai tukar rupiah, suku bunga SBI, dan inflasi terhadap indeks harga saham gabungan (IHSG) sektor pertanian di Bursa Efek Indonesia - Agus Jumadil Akbar; Saadah Yuliana; Taufiq Marwa (Department of Development Economics, Universitas Sriwijaya, 2016)
This study aims to investigate the effect of exchange rates, SBI interest rates, and inflation on the composite sector price index (IHSG) of the agricultural sector with the observation period from January 2009 to December 2013. The data used in this study is secondary data consisting of monthly value data IHSG in the agricultural sector and macroeconomic variables including exchange rates, SBI interest rates and inflation rates. The analytical method used is a quantitative approach by applying multiple linear regression models with the method of estimating ordinary least square. The results showed that the exchange rate and SBI interest rates significantly affected the composite stock price index (IHSG) of the agricultural sector in the form of negative effects. While the inflation rate does not significantly affect the composite stock price index (IHSG) of the agricultural sector